ﺣﻤﻠﺔ 100 ﻣﻠﯿﻮن ﺻﺤﺔ - Ghalab, Riham Adel (2019)
As part of the IFPRI Egypt Seminar in partnership with the National Nutrition Committee: "the 100 million healthy lives initiative: Food availability, access and consumption patterns in Egypt"